Relation issue between budgeting and management accounting - Koliesnichenko, Anastasiia (Baltija Publishing, Latvia, 2019)
Budgeting and management accounting processes are part of one whole mechanism aimed at realization of internal business processes in the enterprise with the purpose of achievement of the set goals of functioning and fulfillment of its mission. Effective management of the market subject in modern development conditions is heavily dependent on the quality and speed of use of these components.
Keywords: management; accounting; budgeting; business processes